Tinjauan Terhadap Kepemimpinan Suatu Review Literatur Terhadap Efektivitas Pemimpin Tingkat Kelurahan dan Desa Di Sulawesi Selatan - Pelita, Andi (Jurnal Ilmiah Administrasita, 2015)
The research is a conceptual framework that is developed based on the literature review and initial prelimanary research using interview method to build the framework of the relationship between leadership of the village head and organizational performance in Sinjai Regency. On the basis of emperical findings from initial study and literature review, it was found that there are relationship between leadership skills, leadership style, and self-eladership towards organizational performance.